Osteomielitis por Shewanella putrefaciens: reporte de caso y revisión de literatura - Guinetti-Ortiz, Katia (2016)
Shewanella putrefaciens is a Gram-negative bacillus and marine pathogen that rarely causes disease in humans. We report a case of osteomyelitis by this organism in a 48-year-old male patient, who presented with pain and erythema of the right foot that was initially diagnosed as cellulitis and did not revert despite treatment. He was transferred to Lima where osteomyelitis was diagnosed and started on empirical treatment with partial regression. A biopsy and culture of the compromised area found S. putrefaciens. The infection was treated according to the antibiotic sensitivity profile of the pathogen. S. putrefaciens infection represents a rare opportunistic infection of devitalized or exposed areas of the body. It is associated with residence in coastal areas and commonly affects the skin and soft tissues. Exceptional cases of osteomyelitis have been reported, but this is the first that involves the metatarsal bones. Shewanella putrefaciens es un bacilo Gram negativo, patógeno marino que rara vez ocasiona enfermedad en humanos. Se presenta un caso de osteomielitis por este microorganismo en un paciente varón de 48 años, procedente de Chimbote. Presentó dolor y eritema en el pie derecho, inicialmente diagnosticado como celulitis, pero que no revirtió pese al tratamiento. Fue transferido a Lima donde se diagnosticó osteomielitis e inició tratamiento empírico con escasa mejoría. Por ello, se realizó una biopsia y cultivo de la zona comprometida, el metatarso, en el cual se aisló Shewanella putrefaciens. Se trató de acuerdo al perfil de sensibilidad. La infección por Shewanella putrefaciens representa una rara infección oportunista, que se localiza en áreas desvitalizadas o expuestas del cuerpo. Se asocia a vivir en zonas costeras, afectando comúnmente piel y tejidos blandos. Se han reportado casos excepcionales de osteomielitis. Este es el primero que involucra metatarso.